The professional moratorium of teaching: a sociological essay - Gilson Ricardo de Medeiros Pereira; Maria da Conceição Lima de Andrade (Universidade Federal de Santa Catarina, 2009)
The purpose of this article is to analyze the professionalization of teaching in the current state of Brazilian education. The analysis looked at recruitment, that is the conditions of choosing this specific occupation; initial education, that is, the processes by which the necessary physical and cognitive dispositions are incorporated to this profession; and continued education, or the continuous restructuring of these dispositions. The professional exercise is defined as action based on strategies guided by objectives, which require different forms of knowledge incorporated by guaranteed and institutionally legitimated means, and as actions guided by an ethics capable of regulating behavior in the exercise of professional activities. It is based on the understanding that the opposition between "cognitive realization" and "moral realization" commands the recruitment of teachers and in many ways, conditions their professionaliza- tion process. Once confronted with another index, the educa-tional output of the agents themselves, the opposition mentioned allows clarifying the current situation of recruitment for entrance into the teaching profession, above all in its lowest positions, that of elementary school education, and makes it possible to understand the subsequent developments of professionalization in the modalities of initial and continued education.